Intranasal delivery of hMSC-derived supernatant for treatment of ischemic stroke by inhibiting the pro-inflammatory polarization of neutrophils - Yixiang Jiang; Ning Wang; Jingyi Liu; Haoran Ren; Wenkang Jiang; Yanting Lei; Xidan Fu; Miao Hao; Xiujuan Lang; Yumei Liu; Xijun Liu; Rui Li; et al. (Stem Cell Research & Therapy)
Abstract Background Stem cells utilized for ischemic stroke treatment often display unstable homing capabilities and diminished activity in vivo, limiting their neuroprotective efficacy. Furthermore, the optimal delivery route for stem cells remains undetermined. While the cytokines secreted by stem cells show promise in modulating post-stroke inflammation, the direct application of these supernatants in ischemic stroke treatment and the underlying mechanisms are still unclear. Methods Secretory supernatants (hMSC-L) and cell lysate products (hMSC-M) from primary human umbilical cord mesenchymal stem cells-cultured medium were administered intranasally to mice with cerebral ischemia. The neuroprotective effects of hMSC-L and hMSC-M were assessed with TTC staining, behavioral tests and pathological staining. Flow cytometry and qPCR evaluated the expression of immune cells and cytokines in the CNS and peripheral immune organs. In vitro, flow cytometry and ELISA measured the effects of hMSC-L and hMSC-M on N2 polarization and inflammatory cytokines expression in primary murine neutrophils. Western blot analysis determined the impact of hMSC-L and hMSC-M on the PPAR-γ/STAT6/SOCS1 pathway, which is crucial for N2 neutrophil polarization. Results TTC staining, behavioral experiments, and pathological assessments reveal intranasal delivery of hMSC-L and hMSC-M significantly reduces the infarct volume of mice with cerebral ischemia, improves neurological function scores, and promotes motor function recovery. Higher concentrations of hMSC-M contributed a more pronounced effect on neuropathological improvements in ischemic mice. Intranasal delivery of hMSC-L and hMSC-M significantly reduces neutrophil infiltration in the brain post-stroke and increases the proportion of anti-inflammatory N2-subtype neutrophils, boosting the expression levels of IL-10 and TGF-β. In vitro experiments demonstrate that hMSC-L and hMSC-M promote nuclear translocation of PPAR-γ in neutrophils stimulated with PMA, activating the downstream STAT6/SOCS1 signaling pathway to encourage N2-subtype neutrophil polarization. Conclusions Intranasal delivery of hMSC-L and hMSC-M effectively ameliorates cerebral ischemic injury in mice, comparable to traditional administration routes like intravenous delivery. Treatment with hMSC-L and hMSC-M enhances the PPAR-γ/STAT6/SOCS1 pathway and improves the neuroinflammatory response post-stroke by increasing N2 neutrophil infiltration. These results provide a theoretical basis for a deeper understanding of the mechanisms of stem cell therapy and for exploring suitable delivery pathways of stem cell treatment.